Potato ecological quality in the biologization of high-intensity technologies of its cultivation and irrigation - Butov A.; Mandrova A. (Техника и технология пищевых производств)
To reduce the accumulation of toxic substances in tubers in 2014–2016 the author studied biological methods of fertilizers application and plant protection in black earth forest-steppe region under the conditions of high-intensity potato cultivation technology along with drip irrigation. The introduction describes the importance of potato in the diet of population and lists the environmental issues that arise as a result of enhanced using of chemicals during crop cultivation. The doses of mineral fertilizers in experiments were introduced separately and in combination with a bioameliorant: 1) without fertilizers (control site); 2) N60P90K60; 3) N90P135K90; 4) N120P180K120; 5) biological ameliorant – white mustard, post-harvest green manure; 6) bioameliorant + N60P90K60; 7) bioameliorant + N90P135K90; 8) bioameliorant + N120P180K120. Chemical insecticide Aktara and biological preparations Fitoverm, Akarin were used to protect potatoes against Colorado potato beetles. Insecto-fungicide Celest was used to treat seed tubers against fungal diseases. During growing season the author used fungicides Profit Gold, Ridomil Gold against fungal diseases, against weeds – Zenkor and Remus. High yield of potato environmentally friendly considering nitrates was obtained by means of simultaneous application of N90P135K90 and white mustard green mass. Tuber yield was 40.4 tonnes per hectare compared to 22.7 tonnes per hectare on the control site, and nitrate content was 111.3 mg while maximum permissible concentration (MPC) is 250 mg/kg. According to MPC established in the Russian Federation, for childrenʼs and dietary nutrition fertilizer dose should not exceed N60P90K60 in combination with a bioameliorant and a biological plant protection system. Safety interval (period between plant treatment and harvesting) for chemical insecticides is 35–40 days; fungicides – 20 days; herbicides (depending on their type) – 55–70 days. The production of ecologically clean potato according to EU standards was achieved only by means of using post-harvest green manure as a fertilizer, applying biological insecticides and Celest preparation within the framework of protecting plants against pests and diseases.